Economic Time Series Forecasting: Box-Jenkins Methodology, Signal Processing and Neural Network Approach - Marcek, Dusan; Acova, Michaela (Communications - Scientific letters of the University of Zilina, 2003)
This paper is devoted to the presentation of methods of economic time series analysis and modelling using the Box-Jenkins methodology, the signal processing approach and the feedforward neural network technique. Some results of our research on time series modelling with emphasis on potential improving forecast accuracy are presented here. The assessment of the particular models has been made using the root mean square error.